Ona ir Marcelė Jurgauskaitės - knygnešės ir daraktorės - Urbonas, Viktoras (Knygotyra, 1997)
Ona and Marcelė Jurgauskaitė were enlighteners of the Lithuanian people at the end of the 19th century and the beginning of the 20th. Their activities left an impressive mark in the Šiaulėnai district and beyond. Ona Jurgauskaitė was a teacher between 1889-1905 in the villages of Šiaulėnai, Žarėnai, Darbėnai, Šimkaičiai, and Tytuvėnai. Marcelė Jurgauskaitė was an active book distributor. She carried forbidden Lithuanian books from Tilžė and distributed them in the towns of Šiaulėnai, Grinkiškis, Baisogala, and Radviliškis. She was also a teacher in the village of Kudinai (district of Šiauliai). Both of them were buried in the cemetery of Šiaulėnai.